Physiological and inflammatory consequences of high and low respiratory rate in acute respiratory distress syndrome. Issue 8 (1st May 2021) - Retamal, Jaime; Damiani, Luis Felipe; Basoalto, Roque; Benites, Martín H.; Bruhn, Alejandro; Larsson, Anders; Bugedo, Guillermo
Abstract : Using protective mechanical ventilation strategies with low tidal volume is usually accompanied by an increment of respiratory rate to maintain adequate alveolar ventilation. However, there is no robust data that support the safety of a high respiratory rate concerning ventilator‐induced lung injury. Several experimental animal studies have explored the effects of respiratory rate over lung physiology, using a wide range of frequencies and different models. Clinical evidence is scarce and restricted to the physiological impact of increased respiratory rate. Undoubtedly, the respiratory rate can influence respiratory mechanics in various ways as a factor of multiplication of the power of ventilation, and gas exchange, and also on alveolar dynamics. In this narrative review, we present our point of view over the main experimental and clinical evidence available regarding the effect of respiratory rate on ventilator‐induced lung injury development.